Students’ Satisfaction and Motivation in Learning Grammar mediated by Quizizz - Rahmadani, Nur; Rahman, Faisal; Swastina, Liliana (CV. Tripe Konsultan, 2022)
The development of education in Indonesia is growing rapidly along with technological advances. The use of technology can be an excellent supporter in learning English in universities. Learning media such as online quiz applications should be an alternative way to teach foreign languages, especially English. The focus of this research was to identify the students' satisfaction and motivation in learning grammar mediated by Quizizz. This research used a qualitative approach through sampling techniques with Saturated Sampling (census) on English Language Education Study Program at Sari Mulia University in Banjarmasin, South Kalimantan. From the results obtained through interviews and questionnaires, each student has various opinions regarding learning grammar mediated by Quizizz. Students feel satisfied and considered Quizizz is more interesting than other learning media because it is easy to use with an attractive appearance and it is self-paced so each student gets a chance to answer without feeling rushed. Students consider Quizizz to be an easy-to-use application and one of the teaching media that can increase students’ motivation to learn grammar easier even though there are several limitations and problems experienced by students using Quizizz, including the limitations of internet connections but it doesn't make them give up in learning and keep feeling excited.